Kepemimpinan Donald Trump dan Turbulensi Tatanan Dunia - Siswanto, Siswanto (Jurnal Penelitian Politik, 2018)
ABSTRACTThe background of this article is based on the consideration that the policy pursued by America under the leadership of President Donald Trump is controversial, leading to a turbulence of world leadership. Furthermore the issue discussed in this paper is the in-consistent personality of President Donald Trump who encourages of controversial policies. The policy of protecting on national interest (America First) leads to protectionism and America's rebuilding policy (make America great again) encourages diplomatic tension. Apart from that, this paper also discusses the consequences of controversial policy direction towards world leadership turbulence especially in Middle East and Asia. The result of this study is a conclusion formulated that the in-consistent personality that existed in President Trump is a stimulus to the controversial policy and the controversial policy becomes the trigger for the world's leadership turbulence. Finally the recommendation of this paper is be careful in relations with America under President Trump.Keywords: controversy, turbulence, American policy, President of Trump